Identification of dominant structures and their flow dynamics in the turbulent two-phase flow using POD technique - Munir, S. (Korean Society of Mechanical Engineers, 2015)
The Proper orthogonal decomposition (POD) method has seen increasingly used in the last two decades and has a lot of applications for the comparison of experimental and numerically simulated data. The POD technique is often used to extract information about coherent structures dominating the flow. The two-dimensional and two-component instantaneous velocity fields of both liquid and gas phases of a slug flow were obtained by Particle image velocimetry (PIV) combined with Laser induced fluorescence (LIF). POD was applied to the velocity fields of both phases separately to identify the coherent flow structures. We focused on POD eigenmodes and their corresponding energy contents of both liquid and gas phases. The sum of first few eigenmodes that contain maximum turbulent kinetic energy of the flow represents the coherent structures. In the case of liquid phase the first eigenmode contained 42 of the total energy, while in the gas phase the decaying energy distribution was flat. The POD results showed that the coefficient of mode 1 for the liquid phase oscillated between positive and negative values and had the highest amplitude. For the visualization of coherent motion different linear combinations of eigenmodes for liquid and gas phases were used. The phenomena of turbulent bursting events associated with Q2 events (low momentum fluid moving away from the wall) and Q4 events (high momentum flow moving towards the wall) were also discussed to assess its contribution in turbulence production Â© 2015, The Korean Society of Mechanical Engineers and Springer-Verlag Berlin Heidelberg.